2010
DOI: 10.1159/000318605
|View full text |Cite
|
Sign up to set email alerts
|

E-Cadherin and Transglutaminase-1 Epithelial Barrier Restoration Precedes Type IV Collagen Basement Membrane Reconstruction following Vocal Fold Mucosal Injury

Abstract: The vocal fold epithelium is critical to upper airway immunologic defense and water/ion transport; therefore, any form of physical trauma or insult increases the vulnerability of this structure to functional impairment and pathogen invasion/infection. In this study, we examined the reestablishment of epithelial and basement membrane barrier structures in a well-established rat model of vocal fold mucosal injury. We observed active cell recruitment culminating in peak hyperplasia at 3 days postinjury, the estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 78 publications
(64 reference statements)
3
11
0
Order By: Relevance
“…expression of E-cadherin has been demonstrated to reduce tumor progression and invasiveness in addition to the formation of metastases (21,(27)(28)(29)(30). The results from the present study demonstrated that the overexpression of 14-3-3ζ was significantly associated with positive E-cadherin expression in tissue specimens from patients with lung adenocarcinoma and was a prognostic factor, which is in agreement with a number of previous studies that have suggested this association (14,15,31,32).…”
Section: Discussionsupporting
confidence: 92%
“…expression of E-cadherin has been demonstrated to reduce tumor progression and invasiveness in addition to the formation of metastases (21,(27)(28)(29)(30). The results from the present study demonstrated that the overexpression of 14-3-3ζ was significantly associated with positive E-cadherin expression in tissue specimens from patients with lung adenocarcinoma and was a prognostic factor, which is in agreement with a number of previous studies that have suggested this association (14,15,31,32).…”
Section: Discussionsupporting
confidence: 92%
“…Three major groups of cell junctions include occluding, anchoring, and communicating junctions (Table 1). Members of each junction group have been identified in the vocal fold epithelium of humans and numerous animal models using a combination of cellular and molecular biology techniques (Alper, Fu, Erickson-Levendoski, Zheng, & Sivasankar, 2011; Fisher, et al, 2001; Gill, et al, 2005; Hirano et al, 2003; Ling, Raasch, & Welham, 2011; Rousseau, et al, 2011; Schneider, Teschner, Sudermann, Pikula, & Lautermann, 2002; Sivasankar, Erickson, Rosenblat, & Branski, 2010; Van Deusen & Lyon, 2008; Zhang & Fisher, 2012). Alteration in cell junction formation and distribution, destabilization, or all may lead to epithelial barrier dysfunction.…”
Section: Structure Of the Vocal Fold Epithelial Barriermentioning
confidence: 99%
“…However, by day 7, the luminal surface of this thickened epithelium was characterized by decreased cell numbers and partial coverage by squamous-appearing cells. To further investigate epithelial recovery following injury, this group characterized the expression of the adherens junction protein E-cadherin and the protein cross-linking enzyme transglutaminase-1 at the same points as above (Ling, et al, 2011). Like E-cadherin, transglutaminase-1 is important for cell-cell adhesion and epithelial stability.…”
Section: Vocal Fold Epithelial Barrier Injurymentioning
confidence: 99%
“…Indeed, a number of studies have identified a reduced expression of E-cadherin, due to loss of heterozygosity (LOH) at 16q22.1, inactivating mutations, CpG-island hypermethylation of CDH1 gene promoter or silencing of CHD1 gene expression by specific transcription factors, in many epithelial tumours, including breast cancer (BC), pancreatic ductal adenocarcinoma (PDAC), gastric cancer (GC) and colorectal cancer (CRC), as well as hepatocellular carcinoma;31 sqamous cell carcinomas of the skin,32 head and neck;33 oesophageal carcinoma;34 and melanoma 35…”
Section: E-cadherin In Human Cancersmentioning
confidence: 99%